2016
DOI: 10.1007/s12035-016-0084-z
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant-Rich Fraction of Urtica dioica Mediated Rescue of Striatal Mito-Oxidative Damage in MPTP-Induced Behavioral, Cellular, and Neurochemical Alterations in Rats

Abstract: Parkinson's disease (PD) having a complex and multi-factorial neuropathology includes mainly the degeneration of the dopaminergic nigrostriatal pathway, which is a cumulative effect of depleted endogenous antioxidant enzymes, increased oxidative DNA damage, mitochondrial dysfunction, excitotoxicity, and neuroinflammation. The present study was designed to investigate the neuroprotective effect of a potent antioxidant from Urtica dioica in a 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) model of parkinson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 48 publications
1
19
0
1
Order By: Relevance
“…Also, antioxidant actions of selegiline might contribute to its efficiency on memory impairment due to involvement of oxidative stress in the decline of cognition associated with disorders of Neurodegeneration [35]. This was in accordance to Bisht et al [36] who declared that selegiline administration significantly decreased lipid peroxidation and nitrite concentration with increasing the activity of GSH in MPTP-treated rats. Besides, selegiline restored dopamine and its metabolite content as compared to the MPTP-administered group.…”
Section: Discussionsupporting
confidence: 80%
“…Also, antioxidant actions of selegiline might contribute to its efficiency on memory impairment due to involvement of oxidative stress in the decline of cognition associated with disorders of Neurodegeneration [35]. This was in accordance to Bisht et al [36] who declared that selegiline administration significantly decreased lipid peroxidation and nitrite concentration with increasing the activity of GSH in MPTP-treated rats. Besides, selegiline restored dopamine and its metabolite content as compared to the MPTP-administered group.…”
Section: Discussionsupporting
confidence: 80%
“… Arctigenin, traxillagenin, and 49-demethyltraxillagenin improved hepatocytes condition by maintaining the GSH level CCl 4 treated rats Liver related problem Kim et al, 2003 Theaceae Camellia sinensis (L.) Kuntze In repeated stress induced rats model the hydroalcohol leaf extract elevated depression condition, improve immobility condition, oestrogen level and glucose metabolism in brain Mental Problem Ye et al, 2019 Pre-treatment of aqueous leave extract significantly reduced oxidative damage, urea, uric acid and creatinine level and showed good antioxidant effect in nicotine treated rats Kidney complications Saad et al, 2019 Leaves and its major phytoconstituents such as, catechin, epicatechin and epigallocatechin gallate improved Parkinson's disease condition in in-vivo model Parkinsonism Pinto et al, 2015 Aqueous leaf extract showed reduction of enzyme and non-enzyme levels of liver tissues and lipid peroxidation in CCl 4 treated rat Liver related problem Hy and Ira, 2015 Consumption of the plant effectively could manage cardiovascular risk factors Cardiac complications Deka and Vita, 2011 Extract of the plant increased NO, TNF-α level, reduced the degree of injury and infiltration of neutrophil tissues in carrageenan-treated mice Lung related complications Paola et al, 2005 Urtiaceae Urtica dioica L. Hydroalcohol leave extract improved anti-depressant and anxiolytic condition in-vivo study. Mental Problem Patel et al, 2018 Hydroalcohol extract improved motor function, mito-oxidative defense alteration in Parkinson's disease induced rat model Parkinsonism Bisht et al, 2017 Aqueous extract inhibited eosinophilia, leucocytes, lymphocytes levels and lipid peroxidation in BALF in asthmatic rats Lung related complications Zemmouri et al, 2017 Ethanol extract improved nephrotoxic condition by decreasing serum creatinine and blood urea nitrogen level in nephrotoxic rabbit model Kidney complications …”
Section: Herbal Formulae From Different Traditional Systems Of Medicinementioning
confidence: 99%
“…Several studies have established that extracts of U. dioica possess various pharmacological effects [37,38,39], including anti-inflammatory [40,41,42], anti-oxidant [43,44,45,46,47], anti-microbial [46,47,48,49], anti-diabetic [39,50,51], cardiovascular [39], anti-ulcer, analgesic [36], immuno-modulatory [35,52], anti-mutagenic [44] and anti-cancer properties. Moreover, this edible plant has considerable chemopreventive capacities and disease-preventing effects on animals and humans.…”
Section: Phytochemical Investigations and Biological Activities Ofmentioning
confidence: 99%
“…The anti-oxidant and radical scavenging activities of U. dioica were reported by ABTS and superoxide-radical scavenger assays and on analysis of the changes in antioxidant enzymes [43,44,45,46,47]. In mice, the treatment with U. dioica methanolic extract from the aerial parts demonstrated hepatoprotective and nephroprotective activities against cisplatin-induced [74,75] toxicity, most likely due to increasing antioxidant defense mechanisms, in fact, this extract has been shown to increase the activities of catalase (CAT) and superoxide dismutase (SOD) enzymes and the content of glutathione (GSH) [76].…”
Section: Anticancer Activities Of Urtica Dioicamentioning
confidence: 99%